2013
DOI: 10.1021/jf3050268
|View full text |Cite
|
Sign up to set email alerts
|

Chicoric Acid Induces Apoptosis in 3T3-L1 Preadipocytes through ROS-Mediated PI3K/Akt and MAPK Signaling Pathways

Abstract: Chicoric acid has been reported to possess various bioactivities. However, the antiobesity effects of chicoric acid remain poorly understood. In this study, we investigated the effects of chicoric acid on 3T3-L1 preadipocytes and its molecular mechanisms of apoptosis. Chicoric acid inhibited cell viability and induced apoptosis in 3T3-L1 preadipocytes which was characterized by chromatin condensation and poly ADP-ribose-polymerase (PARP) cleavage. Mitochondrial membrane potential (MMP) loss, Bax/Bcl-2 dysregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 58 publications
2
54
0
Order By: Relevance
“…The results of the present study suggest that chicoric acid has a protective effect following cerebral I/R injury, ameliorating increases in ROS generation, inflammation and NO and COX-2 levels in rats. It has also been reported that chicoric acid induces the apoptosis of 3T3-L1 preadipocytes and mediates COX-2, ROS, PI3K/AKT and p38-MAPK signaling pathways (13). Kour and Bani (11) revealed that chicoric acid suppressed inflammation in chronically stressed mice.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of the present study suggest that chicoric acid has a protective effect following cerebral I/R injury, ameliorating increases in ROS generation, inflammation and NO and COX-2 levels in rats. It has also been reported that chicoric acid induces the apoptosis of 3T3-L1 preadipocytes and mediates COX-2, ROS, PI3K/AKT and p38-MAPK signaling pathways (13). Kour and Bani (11) revealed that chicoric acid suppressed inflammation in chronically stressed mice.…”
Section: Discussionmentioning
confidence: 94%
“…Chicoric acid induces the apoptosis of 3T3-L1 preadipocytes and mediates ROS, MAPK pathway mediates the anti-oxidative effect of chicoric acid against cerebral ischemia-reperfusion injury in vivo phosphatidylinositide 3-kinases (PI3K)/protein kinase B (AKT) and p38-mitogen-activated protein kinase (MAPK) signaling pathways (12,13). The aim of the present study was to investigate the protective effect of chicoric acid on oxidative stress and inflammation in rats with cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt and MAPK signaling pathways have been shown to be activated by ROS (16,19,21). In other studies, NF-B and HIF-1␣ are shown to be the downstream targets of PI3K/Akt and/or ERK (22)(23)(24).…”
Section: Activation Of Nf-b and Hif-1␣ Involves Ros-mediated Activatimentioning
confidence: 90%
“…Chicoric acid properties have been reported to include anti-cancer, anti-obesity, antiviral, and anti-diabetic (King and Robinson, 1998; Pluymers et al, 2000; Charvat et al, 2006; Queffelec et al, 2008; Tousch et al, 2008; Tsai et al, 2012; Azay-Milhau et al, 2013; Xiao et al, 2013). For example, chicoric acid and its analogs have been claimed to possess anti-Human Immunodeficiency Virus (HIV) activity due to its involvement in HIV integrase inhibition, which could perhaps hinder HIV strain replication (King and Robinson, 1998; Charvat et al, 2006; Queffelec et al, 2008).…”
Section: Biological Activities Of Chicoric Acidmentioning
confidence: 99%